Application of the "Foot-in-the-Door" Compliance Technique for Traveler Intercept Surveys. Issue 42 (December 2018) - Sperry, Benjamin R.; Siler, Emily; Mull, Tristan
Traveler intercept surveys are used to obtain essential data for transportation planning purposes in a variety of contexts and situations. This paper describes an application of the foot-in-the-door (FITD) compliance technique for traveler intercept surveys as a way to increase participation and improve the overall experience for both the traveler and the organization conducting the survey. Outcomes related to survey participation and response characteristics for three such surveys are presented. The two-stage FITD method described in this paper was successful at collecting a small amount of data from a majority of travelers at the locations being studied while minimizing the inconvenience to the traveler. A follow-up survey conducted via the Internet had a response rate that varied between the different case studies and also among different groups of travelers. Approximately one-third of follow-up survey responses were provided on the same day as the initial interaction between the traveler and the researcher, whereas one-quarter of respondents utilized a mobile device to complete the follow-up survey. The results of these case studies are informative for the development of traveler intercept surveys. Transportation planners are encouraged to consider the FITD technique described in this paper when developing traveler intercept surveys within their jurisdictions.